2012
DOI: 10.3233/jad-2012-120688
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Mediated Neuroprotection Against Amyloid-β-Induced Mitochondrial Dysfunction Involves the Inhibition of GSK-3β

Abstract: The deposition of amyloid-β (Aβ) peptides in senile plaques is one of pathological hallmarks of Alzheimer's disease (AD). Mitochondrial dysfunction is an early event of cell apoptosis. Increasing evidence indicates that Aβ induces neuronal apoptosis through mitochondrial dysfunction. Curcumin, an anti-oxidative component of turmeric (Curcuma longa), has shown anti-tumor, anti-inflammatory, and anti-oxidative properties. In this study, we investigated the protective effects of curcumin against mitochondrial dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 42 publications
0
53
1
Order By: Relevance
“…Among the four tested phytochemicals, only ()Sch B and EGCG were found to protect against A-induced apoptosis in SH-SY5Y cells. However, other reports have demonstrated that Cur and Rev can protect against -induced toxicity in primary neurons and neuroblastoma cells [28,29]. The discrepancy between the present study and earlier studies by other laboratories may be related to differences in drug treatment protocols.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Among the four tested phytochemicals, only ()Sch B and EGCG were found to protect against A-induced apoptosis in SH-SY5Y cells. However, other reports have demonstrated that Cur and Rev can protect against -induced toxicity in primary neurons and neuroblastoma cells [28,29]. The discrepancy between the present study and earlier studies by other laboratories may be related to differences in drug treatment protocols.…”
Section: Discussioncontrasting
confidence: 57%
“…The discrepancy between the present study and earlier studies by other laboratories may be related to differences in drug treatment protocols. In previous studies, exposure to Cur or Rev was immediately followed by challenge [28,29], whereas in the present study, phytochemical-pre-incubated cells were further incubated with fresh medium without phytochemicals for 16 h before being subjected to  challenge. The glutathione antioxidant response, if it occurs, is elicited during the post-drug exposure incubation period.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that curcumin treatment attenuates pathological conditions through activation of prosurvival signaling pathways [26,27]. To a large extent, these protective effects of curcumin have been attributed to its strong activity against mitochondrial dysfunction [28,29]. Because of its potent antioxidant properties and an anti-apoptotic activity in noncancerous cells, we hypothesized that curcumin might effectively protect osteoblasts from oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, co-treatment with ME and LY294002 failed to result in a significant inhibition of phosphorylation. In addition, GSK-3β promotes ROS generation and intrinsic apoptotic signaling, which is often induced by intracellular damage that leads to mitochondrial release of cytochrome c and the activation of intracellular cysteine proteases known as caspases, eventually resulting in apoptosis (Huang et al, 2012;Mines et al, 2011). In this study, ME treatment reduced oxidative stress, which generally contributes to apoptosis (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 88%